Exchange Rate or Wage Changes in International Adjustment? Japan and China versus the United States - Ronald McKinnon (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Under the world dollar standard, a discrete appreciation by a dollar creditor country of the United States, such as China or Japan, has no predictable effect on its trade surplus. Currency appreciation by the creditor country will slow its economic growth and eventually cause deflation but cannot compensate for a savinginvestment imbalance in the United States. Under a fixed exchange rate, however, differential adjustment in the rate of growth of money wages will more accurately reflect international differences in productivity growth. International competitiveness will be better balanced between high-growth and low-growth economies, as between Japan and the U.S. from in 1950 to 1971 and China and the U.S. from 1994 to 2005, when the peripheral country?s dollar exchange rate is fixed so that its wage growth better reflects its higher productivity growth. The qualified case for China moving toward greater flexibility in the form of a very narrow band for the yuan/dollar exchange rate, as a way of decentralizing foreign exchange transacting, is discussed.
Keywords: F15; F31; F33; 330; exchange rate; dollar standard; trade balance; China; Japan; Internationales Währungssystem; Handelsbilanz; Wechselkurspolitik; Internationale Währungspolitik; Wirtschaftslage; USA; Japan; China